PREDICTIONS AND TRENDS PROFITABILITY FOR ISLAMIC COMMERCIAL BANKS IN INDONESIA DURING THE COVID-19 PANDEMIC - Afkar, Taudlikhul; Fauziyah, Fauziyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study is to determine trends and predict the level of profitability of Islamic banks in Indonesia during the Covid-19 pandemic. The research method uses quantitative descriptive to explain trends and quadratic analysis techniques to predict profitability. Islamic commercial banks in Indonesia were used entirely as samples in this study. Observation of data used before and during the Covid-19 pandemic starting from 2019-2020 in a time series. The results showed that during the Covid-19 pandemic, Islamic banks were still able to generate profits even though they experienced a downward trend, while the predictions of profitability during the Covid-19 pandemic in 2021 showed an average decline and losses.